THE RELATIONSHIP BETWEEN EATING PATTERNS, FAMILY SIZE, AND PERSONAL HYGIENE WITH THE NUTRITIONAL STATUS OF ELEMENTARY SCHOOL CHILDREN IN GRADES 4-6 IN ARONGAN LAMBALEK DISTRICT - Dewi Martina; Sufyan Anwar; Suci Eka Putri; Wardah Iskandar (PT. Radja Intercontinental Publishing, 2025)
School-aged children are a vulnerable group for nutritional disorders because they are in a period of rapid growth and development, requiring a balanced intake of nutrients. In Arongan Lambalek Subdistrict, West Aceh Regency, cases of undernutrition are still found among elementary school children, which are suspected to be influenced by irregular eating patterns, large family size, and suboptimal personal hygiene practices. This study aims to examine the relationship between eating patterns, family size, and personal hygiene with the nutritional status of elementary school children in grades 4–6 in Arongan Lambalek Subdistrict. The research employed an analytical survey with a cross-sectional approach. The population consisted of all students in grades 4–6 at SDN Arongan Wolya, MIN 5 Aceh Barat, MIN 12 Aceh Barat, SDN Drien Rampak, SDN Keub, and SDN Teupin Peuraho, with a total sample of 235 students selected using total sampling. Data were collected using a Food Frequency Questionnaire (FFQ) for eating patterns, a family size questionnaire, and a personal hygiene questionnaire, while nutritional status was measured based on weight-for-height (BB/TB). Data analysis was performed using the chi-square test. The results showed p-values of 0.000 for eating patterns, 0.000 for family size, and 0.004 for personal hygiene. The study concluded that eating patterns, family size, and personal hygiene were significantly associated with the nutritional status of elementary school children. It is recommended that schools and parents increase attention to children's eating habits and personal hygiene through regular nutrition and health education. Future researchers are advised to include additional variables such as nutritional knowledge and socioeconomic status to obtain a more comprehensive understanding of the factors affecting the nutritional status of elementary school children.